2010
DOI: 10.1136/gut.2010.216671
|View full text |Cite
|
Sign up to set email alerts
|

Nanoliposomal ceramide prevents in vivo growth of hepatocellular carcinoma

Abstract: These studies show that nanoliposomal ceramide is an efficacious antineoplastic agent for the treatment of in vitro and in vivo models of human HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 36 publications
(34 reference statements)
0
68
0
Order By: Relevance
“…We have previously reported that Lip-C 6 induces cytotoxicity in a variety of cancer cell lines. 2,10,11,18,19 In this study, we evaluated the ability of Lip-C 6 , gemcitabine and Lip-PDMP, to trigger cell death of PANC-1 pancreatic cancer cells. ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported that Lip-C 6 induces cytotoxicity in a variety of cancer cell lines. 2,10,11,18,19 In this study, we evaluated the ability of Lip-C 6 , gemcitabine and Lip-PDMP, to trigger cell death of PANC-1 pancreatic cancer cells. ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Recent reports have established the utility of ceramide delivery in nanoliposomes for the systemic treatment of breast cancer, hepatocellular carcinoma, large granular lymphocytic leukemia and melanoma animal models. 2,10,11,18,19 The Nanotechnology Characterization Laboratory of the National Cancer Institute has recently reported the pharmacokinetic profile, and the lack of toxicology, of ceramide-enriched nanoliposomes (http://ncl.cancer.gov/MK_022207_073007.pdf). Further limitations of ceramide as an anticancer therapeutic arises from metabolism into pro-mitogenic phosphorylated derivatives (ceramide-1-phosphate and sphingosine-1-phosphate), which have been implicated in multidrug resistant cellular phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, ceramide can inhibit PI3K/Akt cell signaling and when delivered in nanoliposomes, counteract the Warburg effect in cancer (Y. Jiang et al, 2011; Ryland et al, 2013; Tagaram et al, 2011). It is reasonable to speculate that different populations of exosomes – for example, depending on their ceramide content - may reprogram metabolism of cancer cells in distinct ways.…”
Section: Exosomes In Cancer: Target Tissue Biohacking and Hijacking Omentioning
confidence: 99%
“…Ceramide is able to target the metastatic cascade at multiple points by inducing anoikis and inhibiting extravasation. Taken together, our data suggest that ceramide analogs may be useful not only in treating early stage solid tumors (9,19,36,37), but also in preventing and treating late stage, metastatic carcinoma.…”
Section: Discussionmentioning
confidence: 58%